(untitled) (Bangladesh Journal of Child Health, 2021)
Cockayne syndrome (CS) is a genetic disorder characterized by growth failure, microcephaly, cognitive delay, visual and hearing disorders. Patients usually present with dysmorphism and global delay. It is an autosomal recessive disorder, mutation of two genes ERCC8 and ERCC6 were observed. We report a 4 year old child who was diagnosed as a case of Cockayne syndrome, based on clinical, neuroimaging and genetic study findings. This case had growth failure, dysmorphism, optic atrophy, global developmental delay, intracerebral calcification and mutation of ERCC8 gene. Bangladesh J Child Health 2020; VOL 44 (3) :181-183